Landscape scale control of selected mammalian predators fails to protect lizards - Joanne M. Monks; Anne A. Besson; Colin F. J. O’Donnell (Biological Invasions, 2024)
Invasive mammalian predators are a global biodiversity problem, particularly in archipelagos in which native fauna evolved in isolation from mammals. Landscape scale management of selected invasive mammalian predators is occurring across Aotearoa New Zealand to protect vulnerable forest birds and bats. In temperate southern beech forests, both predator irruptions and the timing of predator control is driven by mast seeding of beech trees. Relationships between predators targeted in this control, other invasive mammalian predators and other native taxa, particularly lizards and invertebrates, are poorly understood. We monitored southern grass skinks in the Eglinton Valley, Fiordland from 2009 to 2020 alongside monitoring of predators (stoats, rats and mice) in a system where predator control occurred in response to mast seeding. We evaluated relationships between skink abundance and abundance of rats (targeted in predator control operations) and mice (which also prey on small vertebrates like lizards, but are not controlled). Skink abundance declined over time and was negatively correlated with mouse abundance, but not correlated with rat abundance. Current landscape predator control to protect forest birds and bats is likely insufficient to protect ground-dwelling lizards, and may actually be detrimental to lizard populations if controlling the other predators contributes to a mesopredator release of mice. Mice are significant predators of a range of small vertebrates and large invertebrates, yet research into the sustainable suppression of mice to benefit vulnerable native populations is lacking. We strongly advocate for such research in order to deliver conservation management that benefits the full suite of biodiversity.

A New Glider-Compatible Optical Sensor for Dissolved Organic Matter Measurements: Test Case from the NW Mediterranean Sea - Frédéric Cyr; Marc Tedetti; Florent Besson; Laurent Beguery; Andrea M. Doglioli; Anne A. Petrenko; Madeleine Goutx (Frontiers in Marine Science, 2017)

Molecular analysis reveals high compartmentalization in aphid–primary parasitoid networks and low parasitoid sharing between crop and noncrop habitats - Stephane A. P. Derocles; Anne Le Ralec; Mathilde M. Besson; Marion Maret; Alan Walton; Darren M. Evans; Manuel Plantegenest (Molecular Ecology, 2014)
The ecosystem service of insect pest regulation by natural enemies, such as primary parasitoids, may be enhanced by the presence of uncultivated, semi‐natural habitats within agro‐ecosystems, although quantifying such host–parasitoid interactions is difficult. Here, we use rRNA 16S gene sequencing to assess both the level of parasitism by Aphidiinae primary parasitoids and parasitoid identity on a large sample of aphids collected in cultivated and uncultivated agricultural habitats in Western France. We used these data to construct ecological networks to assess the level of compartmentalization between aphid and parasitoid food webs of cultivated and uncultivated habitats. We evaluated the extent to which uncultivated margins provided a resource for parasitoids shared between pest and nonpest aphids. We compared the observed quantitative ecological network described by our molecular approach to an empirical qualitative network based on aphid–parasitoid interactions from traditional rearing data found in the literature. We found that the molecular network was highly compartmentalized and that parasitoid sharing is relatively rare between aphids, especially between crop and noncrop compartments. Moreover, the few cases of putative shared generalist parasitoids were questionable and could be due to the lack of discrimination of cryptic species or from intraspecific host specialization. Our results suggest that apparent competition mediated by Aphidiinae parasitoids is probably rare in agricultural areas and that the contribution of field margins as a source of these biocontrol agents is much more limited than expected. Further large‐scale (spatial and temporal) studies on other crops and noncrop habitats are needed to confirm this.

Thermal dependence of locomotor performance in two cool-temperate lizards - Mya J. Gaby; Anne A. Besson; Chalene N. Bezzina; Amanda J. Caldwell; Sarai Cosgrove; Alison Cree; Steff Haresnape; Kelly M. Hare (Journal of Comparative Physiology A, 2011)